Caste and Social Exclusion of IDPs in Jaffna Society - Thanges, Paramsothy (My University, 2008)
This study provides an empirical case study of caste and social exclusion of war-affected Jaffna society. Initial part of this study developed through secondary and historical information on caste-based exclusion and all other parts present the contemporary caste-based exclusion with special reference to the selected camps of Internally Displaced People / Persons (IDPs) in Jaffna society. One of the key issues examined in this study was overrepresentation of certain ‘low-caste’ status “Panchamar” (five so-called low caste groups) in the IDP population remaining in Welfare centers. Although the war affected all inhabitants of Jaffna irrespective of their caste and class backgrounds, many of the long-term IDPs emerge from the traditionally underprivileged caste groups to the exclusion of people from the numerically large and dominant Vellālar caste. All remaining IDPs in the four welfare centers in Mallakam belonged to the Nalavar and Pallar caste. Access to village Hindu temples controlled by “upper caste” Hindus, access to drinking water from wells owned by “high caste” families and discriminations experienced by the “Panchamars” in the land market are some examples of caste-based exclusion in contemporary Jaffna society. Even though caste is not explicitly recognized in many matters and there is a public denial of the importance of caste by most parties, the educated middle classes in particular, the actual social reality is much more complex and multilayered and demands an understanding that goes beyond the superficial level and official truths whether coming from the state and nonstate actors who are eager to consider every thing to meta-narratives such as terrorism, nationalism and liberation struggle.